Status of geoinformatics education and training in Sub-Saharan Africa: initiatives taken and challenges. Issue 2 (3rd April 2019) - Sumari, Neema S.; Shao, Zhengfeng; Van Genderen, John L.; Musakwa, Walter; Ujoh, Fanan; Washaya, Prosper; Gumbo, Trynos
ABSTRACT: This paper presents an update on some of the activities that have taken place since a World Bank report; "Guidelines for Education and Training in Environmental Information Systems in Sub-Saharan Africa: Some Key Issues" was published and provides details on the current situation. It shows how organizations such as the African Association on Remote Sensing of Environment, International Society of Photogrammetry and Remote Sensing, European Association of Remote Sensing Companies, Group on Earth Observation, and several others have helped to increase manpower resources in the region and strengthened institutional capacity in the field of geoinformatics, through capacity building, technology transfer, international cooperation and the provision of internal African resources. After reviewing what has happened in the field of geoinformatics education and training, we focused on current initiatives taken and challenges in five Sub-Saharan countries: Ethiopia, Nigeria, South Africa, Tanzania, and Zimbabwe. We reviewed GIS education and training in the private sector, government, information communications technology in higher education institutions, GIS application areas and challenges facing GIS education and training. Findings show that; change should involve education stakeholders in all levels of education and curriculum quality, regional and international cooperation through exchange programs, should be a priority for Sub-Saharan Africa countries.